Gospodarska diplomacija majhnih držav v primerjalni perspektivi - Smole, Jure (Teorija in praksa, 2023)
The article seeks to analyse and compare the commercial diplomacy of three small countries – Austria, Slovenia and Serbia. The aim of our research is to establish whether and how various political and economic structures in different countries (Austria with a market-oriented economy, Slovenia as a post-transition country, Serbia as a transition one) influence commercial diplomacy. Comparative analysis based on a large number of interviews conducted with commercial diplomacy actors showed that: (1) the country itself always has an influence regardless of the model used by the said countries for formulating their commercial diplomacy, especially when problems or complications arise in a target market (the ex-post approach); (2) each country analysed faces the same challenges related to commercial diplomacy, which do not arise from their particular economic and political system, but from the international environment and the export/import or investment activities of companies; and (3) as concerns the conceptualisation and operationalisation of commercial diplomacy within the study of diplomacy, there is still a lot of missing research that would allow it to be generally accepted because commercial diplomacy and its associated concepts have yet to be uniformly conceptualised, hierarchised and included in the canon of diplomatic studies in the 20 years since the field started to be actively researched.
Keywords: commercial diplomacy; Diplomacija; diplomatic studies; diplomatske študije; gospodarska diplomacija; Male države